EFEKTIVITAS PENGGUNAAN MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII C MTS LABORATORIUM UIN STS JAMBI - Necia Uci Chayani; Eddy Pahar Harahap; Akhyaruddin Akhyaruddin (Universitas Negeri Makassar, 2024)
The purpose of this study was to describe the effectiveness of using a project-based learning model in writing procedure texts for students in class VII C MTS Laboratorium UIN STS Jambi. The method used in this research is quantitative, with an experimental research type. Data analysis techniques use descriptive and inferential statistics. The results showed that there was a significant difference between the pretest and posttest results in writing student procedure texts, where the value of less than the significance of the t-test obtained was 0.00 <0.05. This proves that the project-based learning model is effective in learning to write procedure texts.